Study of threading dislocations in the plan-view sample of SiGe/Si(001) superlattices by transmission electron microscopy - Atici, Y (Springer, 2005)
Interfacial defects due to a mismatch of 1.378% between substrate and epilayer were examined in a Si(0.67)Ge(0.33)/Si(001) superlattice by transmission electron microscopy (TEM). Plan-view specimens from the superlattice were prepared to investigate the defects in the structure. It was observed that 60 degrees-type misfit dislocations associate with point contrast on and at their ends, This point contrast was found to represent threading dislocations by using tilt experiments in the microscope. Consequently, stereo electron microscopy was used to examine the threading dislocations. It was discovered that the threading dislocations are not on the {111} slip planes but can be almost parallel to the [001] zone axis.
Keywords: threading dislocations; SiGe/Si(001) superlattices; transmission electron microscopy (TEM)